2016
DOI: 10.1007/s11356-016-8018-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of strain isolated from dates (Phœnix dactylifera L.) for enhancing very high gravity ethanol production

Abstract: Ethanol production from by-products of dates in very high gravity was conducted in batch fermentation using two yeasts, Saccharomyces cerevisiae and Zygosaccharomyces rouxii, as well as a native strain: an osmophilic strain of bacteria which was isolated for the first time from the juice of dates (Phoenix dactylifera L.). The phylogenetic analysis based on the 16S ribosomal RNA and gyrB sequence and physiological analysis indicated that the strain identified belongs to the genus of Bacillus, B. amyloliquefacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Concerning efficiency, it increased from 52 and 59% for S2 and S3, respectively, in the monoculture to 68% in the co-culture of S2 and S3. Djelal et al (2017) showed that the fermentation of by-products of dates by co-cultures of the isolated strain B. amyloliquefaciens and Z. rouxii showed an increase of the yield of ethanol by 12.5% compared with the single culture; they also demonstrated that the strain ratio did not affect the results of ethanol productivity. Kalyani et al (2013) observed that the co-culture of S. cerevisiae and Pichia stipitis produced 23% and 38% more ethanol than the amounts produced by S. cerevisiae and P. stipitis in pure cultures.…”
Section: Co-culture Of S2 and S3mentioning
confidence: 97%
See 2 more Smart Citations
“…Concerning efficiency, it increased from 52 and 59% for S2 and S3, respectively, in the monoculture to 68% in the co-culture of S2 and S3. Djelal et al (2017) showed that the fermentation of by-products of dates by co-cultures of the isolated strain B. amyloliquefaciens and Z. rouxii showed an increase of the yield of ethanol by 12.5% compared with the single culture; they also demonstrated that the strain ratio did not affect the results of ethanol productivity. Kalyani et al (2013) observed that the co-culture of S. cerevisiae and Pichia stipitis produced 23% and 38% more ethanol than the amounts produced by S. cerevisiae and P. stipitis in pure cultures.…”
Section: Co-culture Of S2 and S3mentioning
confidence: 97%
“…Various microorganisms of indigenous strains capable of producing ethanol have been isolated from different local sources such as dates (Djelal et al, 2017), different fruits (Lee et al, 2011), cheese whey (Boudjema et al, 2016), sugar cane and beet molasses (Hamouda et al, 2016). However, strains isolated from the natural substrate gave much better performance than commercial strains (Djelal et al, 2017). It should also be noted that the production of ethanol in cocultures allows higher results than single cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can affect the growth and metabolism of the strain, causing the dehydration and inactivation of protein, which hinder cell cycle and inhibit cell growth (Radmaneshfar et al 2013). Some studies have found that, with the increase of osmotic stress, the cell will actively regulate osmosis that causes intracellular water out ow, shrinking of cells, and even death (Djelal et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The objective was to treat the grey water for agricultural and industrial purposes. Djelal et al (2017) have identified a strain isolated from dates, which is able to enhance high gravity ethanol production.…”
mentioning
confidence: 99%